Design of Novel Nanoemulsion Formulations for Topical Ocular Delivery of Itraconazole: Development, Characterization and In Vitro Bioassay - Saba Mehrandish; Shahla Mirzaeei (Tabriz University of Medical Sciences, 2022)
Purpose: The objective of this study was to design and develop nanoemulsion formulations of Itraconazole (ITZ), a water-insoluble, potent antifungal drug using the spontaneous emulsification method, to improve the ocular delivery and achieve a sustained release of the drug. Methods: The oil was selected on the basis of the ITZ solubility while the surfactant and co-surfactant were selected based on the thermodynamic stability and globule size. Following the selection of components, a pseudo-ternary phase diagram was constructed for the most promising formulation (F11) using benzyl benzoate (BB) as the oil, Eumulgin CO40 as the surfactant, and propylene glycol as the co-surfactant, by the design of experiments (DoE). Results: F7 and F11 formulations were found to have an average globule size of 223.5 ± 10.7 nm and 157.5 ± 14.2 nm, besides thermodynamic stability and suitable physicochemical properties. F11 possessed an almost seven-fold higher cumulative percentage of in vitro released ITZ, in comparison to ITZ aqueous suspension after 24 hours. The release data suggested that the best fitted kinetical model for F11 and F7 was the Higuchi and Korsmeyer-Peppas model. Conclusion: The extended-release of the drug beside an acceptable amount of loaded ITZ suggested that nanoemulsion is suitable for the delivery of the ITZ.